Effect of precooling and acclimation on repeat sprint performance in heat - Brade, C.; Dawson, B.; Wallman, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
To reduce the potential negative effects of heat on exercise performance, practises such as acclimation and the more acute method of precooling have both been used and reported to enhance performance. Acclimation is likely the more powerful of the two methods, but it has yet to be established whether an acclimated individual would perform better if precooling was also done. Therefore, the aim of this study was to determine if precooling would have an additive effect on performance of an acclimated individual during repeat sprint exercise in the heat. Methods: Ten physically active males completed three experimental trials; a Pre Acclimation (Pre Acc) trial and two post acclimation trials, one with precooling (Post Acc + PC) and another without (Post Acc). These trials consisted of a 30 min baseline period followed by a 70 min repeat sprint cycling protocol performed in the heat (~35.0°C and 60% RH) comprising 2 x 30 min periods of exercise and a 10 min half time period. Each half comprised 30 x 4 s maximal sprints interspersed with exercise at varying intensities. Precooling (ice slushy and cooling jacket) was administered during the baseline and half time periods. Separating the pre and post trials were five acclimation sessions (spread over 10 days) involving repeated (increasing from 8 to 12 by the last session) 3 min cycling efforts performed at 80% maximum power output with 1 min of passive rest between. Physiological measures included core (TC) and mean skin temperature (TSk), heart rate (HR), sweat loss, rating of perceived (RPE) exertion and thermal sensation (TS). Performance measures obtained were peak and mean power and work done. Results: Moderate effect sizes suggested a greater amount of work per kg BM (J•kg-1) was done in Post Acc (1st Half, 1606 ± 102; 2nd Half, 1605 ± 71) compared to Pre Acc (1st Half, 1533 ± 153; 2nd Half, 1538 ± 109). Furthermore, several (possible, likely and very likely) smallest worthwhile effects were found between these conditions, suggesting benefits in Post Acc. Post Acc + PC performance was not different to either Pre Acc or Post Acc. Moderate to strong effect sizes also suggested lower TC (0.2-0.3°C) in the Post Acc + PC and Post Acc compared to the Pre Acc, particularly over the second half of exercise. Sweat Loss was significantly higher (p<0.05: 23.1%) in Post Acc + PC compared to the other two conditions. No significant differences were observed for TSk, HR, RPE or TS. Discussion: Here, a short term (partial) heat acclimation protocol was beneficial for repeat sprint performance in the heat. Greater improvement may have been seen if full acclimation was undertaken. In addition, no further enhancement of performance was seen as a result of acclimated individuals precooling prior to performance, but this did produce a higher sweat loss.